Can biomechanical diagnostic profiling identify the effectiveness of specific training exercises? - Marshall, B.; Moran, K. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
This study investigated the use of a diagnostic and prescriptive pathway that aims to determine the effectiveness of specific training exercises. The model was tested by examining if the effects of drop jump (DJ) training on countermovement jump (CMJ) performance could be explained by the degree to which performance determining factors (PDFs) for the CMJ were overloaded. Participants trained with DJ for 8 weeks yet no change in CMJ performance occurred. Of the 4 CMJ PDFs identified only hip rate of power development was overloaded by the DJ and none were enhanced with training. The results imply that the pathway was effective in identifying whether DJ training would enhance participants CMJ performance. The model could be used to determine if a given exercise would enhance a specific group of athletes prior to initiating training.